The Road Towards “Zero Energy” in Buildings: Lessons Learned from SOLARXXI Building in Portugal - Aelenei, Laura Elena (2010)
In this paper the authors intend to share the lessons learned in the designing process of a solar office building currently underway to reach the Net Zero-Energy performance. Solar XXI building was built in Lisbon in 2006 as a demonstration project [1]. The building, which design is based on a combination of passive design techniques with renewable energy technologies (PV, solar collectors), may be currently considered, from this perspective, a near Net Zero Energy Building. Despite Solar XXI falling short the NZEB status, it is believed that the experience acquired and lessons learned in the designing phase are worth noting. The demonstration of the building energy performance is done by means of experimental monitoring data and energy modelling results using the simulation engine EnergyPlus [2]. In addition of this, it is important to stress out the fact that the authors of this paper, who are participants in the SHC Task 40-ECBCS Annex 52, “Towards Net Zero Solar Energy Buildings” are currently engaged in studying possible strategies for “upgrading” Solar XXI to NZEB status [3].